ANALYSIS OF JUNK FOOD CONSUMPTION BEHAVIOR ON ADOLESCENT HEALTH USING BODY MASS INDEX (CASE STUDY ON STUDENTS OF SMP AL-WASIYAH 30 MEDAN) - Chairul Imam; Putra Apriyadi Siregar (CV. Adiba Aisha Amira, 2023)
Increasing prosperity, technological progress and westernization can lead to changes in lifestyle and eating patterns in the community, especially teenagers who tend to like fast food (junk food) as well as a decrease in physical activity which can increase the occurrence of excess nutrition. The nutritional needs of adolescents need to be considered because during adolescence there is rapid growth and development. Unhealthy eating habits will affect adolescent nutritional intake. Unhealthy foods such as fast food are consumed by many teenagers. At a time when everything is modern like now, teenagers want everything to be fast-paced, including choosing food. Fast food is also known to the public as junk food. Junk food is defined as junk food or food that has no nutrition for the body. Eating junk food is not only useless, but can also damage health. Fast food comes from western countries which generally contain high fat and calories. This research is an analytic descriptive study with a cross sectional approach. The population size is 654 students. The sample consisted of 80 respondents, namely grade 7 and 9 students at SMP Al- Wasliyah 30 Medan, who were randomly selected according to the proportion of each class. Statistical test analysis using the Spearman Rank Correlation test and Chi Square. The results showed that there was a relationship between fast food consumption habits (p=0.038;ρ=0.232), television viewing time (p=0.037; ρ=0.233), total energy consumption (p=0.001; ρ= -0.592), carbohydrate consumption ( p = 0.001; ρ= -0.604), consumption of protein (p=0.001; ρ= - 0.567), consumption of fat (p=0.001; ρ= -0.397) and knowledge of nutrition (p=0.009; ρ=0.289) with Mass Index Body (BMI). There was no relationship between sleep duration, playing computer/video games, exercise habits, carbohydrate consumption, fat consumption, pocket money, parental income, mother's education level, and gender with Body Mass Index (BMI). Suggestions for schools are to carry out educational efforts through health education and to monitor the nutritional status of students through anthropometric measurements.